Endothelial calcium dynamics, connexin channels and blood–brain barrier function - De Bock, Marijke; Wang, Nan; Decrock, Elke; Bol, Mélissa; Gadicherla, Ashish K.; Culot, Maxime; Cecchelli, Romeo; Bultynck, Geert; Leybaert, Luc (Progress in neurobiology, 2013)
Situated between the circulation and the brain, the blood-brain barrier (BBB) protects the brain from circulating toxins while securing a specialized environment for neuro-glial signaling. BBB capillary endothelial cells exhibit low transcytotic activity and a tight, junctional network that, aided by the cytoskeleton, restricts paracellular permeability. The latter is subject of extensive research as it relates to neuropathology, edema and inflammation. A key determinant in regulating paracellular permeability is the endothelial cytoplasmic Ca(2+) concentration ([Ca(2+)]i) that affects junctional and cytoskeletal proteins. Ca(2+) signals are not one-time events restricted to a single cell but often appear as oscillatory [Ca(2+)]i changes that may propagate between cells as intercellular Ca(2+) waves. The effect of Ca(2+) oscillations/waves on BBB function is largely unknown and we here review current evidence on how [Ca(2+)]i dynamics influence BBB permeability.